Deregulation of Factor H by Factor H-Related Protein 1 Depends on Sialylation of Host Surfaces - Dopler, Arthur; Stibitzky, Selina; Hevey, Rachel; Mannes, Marco; Guariento, Mara; Höchsmann, Britta; Schrezenmeier, Hubert; Ricklin, Daniel; Schmidt, Christoph Q. (Frontiers in Immunology, 2021)
For discriminating between self and non-self surfaces and enabling immune surveillance, the complement system relies on the interplay between surface-directed activators and regulators. The dimeric modulator FHR-1 is thought to competitively remove the complement regulator FH from surfaces that strongly fix opsonic C3b molecules - a process known as ‘deregulation’. The C-terminal regions of both proteins provide the basis of this competition. They contain binding sites for C3b and host surface markers and are identical except for two substitutions: S1191L and V1197A (i.e. FH ‘SV’; FHR-1 ‘LA’). Intriguingly, an FHR-1 variant featuring the ‘SV’ combination of FH predisposes to atypical hemolytic uremic syndrome (aHUS). The functional impact of these mutations on complement (de)regulation, and their pathophysiological consequences, have largely remained elusive. Here we address these questions using recombinantly expressed wildtype, mutated and truncation versions of FHR-1 and FH. The ‘SV’ to ‘LA’ substitutions did not affect glycosaminoglycan recognition while having only a small effect on C3b binding. However, the two amino acids largely affect binding of FH and FHR-1 to α2,3-linked sialic acids as host surfaces markers, with the S-to-L substitution causing an almost complete loss of recognition. Even with sialic acid-binding constructs, notable deregulation was only detected on host but not on foreign cells. The aHUS-associated ‘SV’ mutation converts FHR-1 into a sialic acid binder which, supported by its dimeric nature, enables excessive FH deregulation and, thus, complement activation on host surfaces. While we also observed inhibitory activities of FHR-1 on C3 and C5 convertases, the required high concentrations render the physiological impact uncertain. In conclusion, the SV-to-LA substitution in the C-terminal regions of FH and FHR-1 abolishes the sialic acid-binding property and results in an FHR-1 molecule that only moderately deregulates FH. Such FH deregulation by FHR-1 only occurs on host/host-like surfaces that recruit FH. Conversion of FHR-1 into a sialic acid binder potentiates the deregulatory capacity of FHR-1 and thus explains the pathophysiology of the aHUS-associated FHR-1 ‘SV’ variant.